Chemotherapy of breast cancer cells alters susceptibility to complement-mediated opsonization and killing - Nasraa, Mohamed H.; Riad, Mahmoud; Kirschfink, Michael (Medical oncology, 2025)
Resistance of cancer cells to immune-mediated killing poses a significant challenge in optimizing therapeutic strategies and minimizing adverse effects during chemotherapy, radiotherapy, and immunotherapy. Consequently, exploring novel biomarkers are critically needed to assess and monitor cancer treatment response, detect toxic side effects early, and guide individualized therapy. We conducted this research to enhance our understand challenges posed by drug resistance in breast cancer treatment where the impact of pretreatment of BT-474 and SKBR-3 breast cancer cell lines with doxorubicin hydrochloride (doxorubicin) and paclitaxel (taxol) on complement-dependent cytotoxicity (CDC) and opsonization was opserveded. Both cell lines were treated with different concentrations of each drug for 24 and 48 h, followed by evaluating expression of membrane-bound complement regulatory proteins (mCRPs), factor H (fH) binding, iC3b opsonization, and cell killing by CDC. Pretreatment with chemotherapeutics led to variable upregulation of mCRPs (CD46, CD55, CD59) and increased fH binding, contributing to reduced cancer cell lysis at both time points. Conversely, iC3b opsonization was enhanced after 48 h of exposure to either drug. Though this work is limited to HER2-positive breast cancer cell lines, our data suggest that though this work is limited to HER2-positive breast cancer cell lines, short-term exposure to chemotherapeutics enhanced their resistance to CDC. However, since they are efficiently opsonized with the iC3b, this could increase their vulnerability to immunological attacks by CDCC) and ADCC. Such unique contribution illuminates a previously unnoticed shift in the immune elimination landscape following chemotherapy and opens doors for enhancing combination immunotherapies.
Online veröffentlicht: 19. Juni 2025
Gesehen am 17.10.2025